The Effect of Altrenogest Treatment Timing and Artificial Lighting on Hastening of Ovulation in Barren Mares - Basri Tek, Hasan (Acta Scientiae Veterinariae, 2019)
Background: The mares are seasonally polyestrous animals that regular ovulatory cycles of mares occur together with increasing day length. Exposure of mares to an artificial photoperiod is the most common and predictable technique that it is used to develop follicular activity early in the year. Follicle activity is minimal in mares during two winter months of January and February in Northern Hemisphere. The main objective of this study was to investigate efficacy of artificial lighting and timing of altrenogest treatment for hastening the ovulation in Thoroughbred mares. Materials, Methods & Results: One hundred and six Thoroughbred mares had different follicle sizes (< 30 mm) was evaluated under four groups. Mares undergoing only reproductive examination were control group Group I (n = 18). The mares has less than 30 mm in diameter folicle applied oral altrenogest (0.044 mg / bw, for 10 days) were grouped according to the month of application: Group II [February; n = 16], Group III [March; n = 57] and Group IV [April; n = 15]. Ultrasonographical examinations performed at the day of admission and repeated twice a week for 15 days. Naturel mating was planned considering to uterine edema (> 35 mm folicle size), and pregnancies were determined at 14, 28 and 50th day postovulation. Statisticaly, mean and standard deviations and general linear model procedure was performed on Minitab 17, and Anova was used to analysis of variance. The averages of the major variations were compared with the Tukey’s multiple comparison test. The factors effecting to pregnancy rate was analyzed by Chi-square test. Correlations were compared with the Pearson correlation test. The effect of initial months on the size of follicle diameter was found to be significant (P = 0.037). Artificial lighting had no effect on the initial follicle diameter (P = 0.919). The initial follicle diameter (P = 0.001) and artificial lighting (P = 0.026) had a significant effect on the time of follicle reaching in 35mm diameter. Initial follicle diameter (P = 0.001), treatment time (P = 0.000), light therapy (P = 0.026) and altrenogest application (P = 0.026) were found to be effective. Initial follicle diameter (P = 0.575), timing of treatment (P = 0.243), light therapy (P = 0.461) and application of altrenogest (P = 0.088) had no significant effect on the diameter of ovulatory follicle. There are positive correlations between the initial follicle diameter and follicle diameter at the end of treatment (P = 0.000; R = 0.399); There is a high positive correlation between the day of reaching 35mm diameter and ovulation day (P = 0.000; r = 0.777); there is a negative correlation between beginning follicle diameter and 35 mm diameter (P = 0.006; r = -0.266) and ovulation day (P = 0.000; r = -0.366). There was a negative correlation between the follicle diameter at the end of the treatment and the 35mm diameter (P = 0.000; r = -0.736) and the day of ovulation (P = 0.000; r = -0.628). These statistical results pointed out that timing of altrenogest treatment and artifial lighting had effectivity on hastening the ovulations in barren mares. Discussion: To evaluate the seasonal effect on follicle diameter, the measurement of the initial follicle diameters is important, which is smaller in February than the following months. The initial follicle diameter is effect on time to reach in 35 mm diameter and ovulation; however, in these mares, ovulation formes in a long time. Regarding the seasonal effect, the success of ovulation depends on treatment time in seasonal months. It is shown that short term altrenogest administration has not shortened interval to the posttreatment ovulation. As a limitation of this study, because there are not enough mares in control group, further studies should be planned for more evaluations.